2007
DOI: 10.1152/japplphysiol.00641.2006
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in left ventricular function and β-receptor responsiveness following prolonged strenuous exercise

Abstract: Sex differences in neuroendocrine and metabolic responses to prolonged strenuous exercise (PSE) have been well documented. The aim of this investigation was to examine sex differences in left ventricular function and cardiac beta-receptor responsiveness following a single bout of PSE. Nine male and eight female triathletes were examined during three separate sessions: before, immediately after, and 24 h following a half-ironman triathlon using dobutamine stress echocardiography. Steady-state graded infusions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 51 publications
2
34
1
Order By: Relevance
“…Our subject population included both male and female participants. In contrast to one previous study (36), we found no significant sex differences in our primary indexes for systolic and diastolic function, allowing for a single-group analysis with sexes combined.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our subject population included both male and female participants. In contrast to one previous study (36), we found no significant sex differences in our primary indexes for systolic and diastolic function, allowing for a single-group analysis with sexes combined.…”
Section: Discussioncontrasting
confidence: 99%
“…A reduction in ␤-adrenergic sensitivity following PE has been reported by others (12,19,36,37,42); however, this is the first study to examine the contribution of exercise intensity and NA to this phenomenon. Data from animal chronic pacing studies (i.e., duration: 3 h to 20 days) have demonstrated significant reductions in ventricular function (1, 25, 44), secondary to reductions in ␤-adrenergic sensitivity and density (31, 35, 44).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Interestingly, a study by Scott et al showed that postexercise AR responsiveness was maintained in women to a greater extent than men following exhaustive exercise. is is a signi�cant �nding given that postexercise AR desentization is hypothesized to be an element of cardiac dysfunction aer acute, exhaustive exercise [112].…”
Section: -Adrenergic Responsivenessmentioning
confidence: 99%